Causal relationship between hypothyroidism and coronary atherosclerotic cardiovascular disease: a bidirectional two-sample Mendelian randomization - Li, Jiarui; Wang, Yihan; Luo, Xiaoting; Meng, Tianwei; Li, Chengjia; Li, Juan; Du, Likun (Frontiers in Cardiovascular Medicine, 2024)
Objective: This study aims to elucidate the causal relationship between hypothyroidism and ASCVD using a bidirectional Mendelian randomization approach. Method: Single nucleotide polymorphisms (SNPs) associated with hypothyroidism were identified and selected as genetic instrumental variables from aggregated data of genome-wide association studies (GWAS). The outcome of interest, ASCVD, included seven conditions: coronary artery disease (CAD), angina pectoris (AP), myocardial infarction (MI), ischemic stroke (IS), and subtypes IS-large artery atherosclerosis (IS-LAA), IS-small vessels (IS-SV), and peripheral artery disease (PAD). MR analysis employed multiple methods—chiefly inverse variance weighting (IVW), along with MR Egger, weighted median, and weighted mode—to assess causality. Cochrane’s Q test was utilized to evaluate heterogeneity in the MR findings. Causal association reliability was assessed using the MR-Egger intercept, MR-PRESSO tests, and leave-one-out analysis. Reverse MR analysis ensued if forward MR identified a positive exposure-outcome association. Moreover, the DAVID database facilitated GO functional and KEGG pathway enrichment analyses of neighboring genes to instrumental variables, exploring potential disease mechanisms. Result: GWAS pooled data yielded 122 SNPs as potential instrumental variables for hypothyroidism. Forward MR analysis, using the IVW method, indicated hypothyroidism as a risk factor for CAD (OR=2.34, 95%CI=1.39–3.94, P=0.001), AP (OR=2.01, 95%CI=1.28–3.16, P=0.002), MI (OR=1.02, 95%CI=1.01–1.04, P=0.004), and IS-SV (OR=6.92, 95%CI=2.45–19.55, P<0.001). However, no significant link was found between hypothyroidism and the remaining three diseases, with sensitivity analysis reinforcing result robustness. In contrast, reverse MR analysis did not corroborate a causal link from ASCVD to hypothyroidism. The R package identified 83 neighboring genes as instrumental variables. GO enrichment analysis via the DAVID database yielded 53 entries, predominantly involving cAMP catabolic processes, protein binding, and signal transduction. KEGG analysis identified 31 pathways, notably those related to Th1/Th2 and Th17 cell differentiation, and Herpes simplex virus 1 infection. Conclusion: The marked association between hypothyroidism and CAD, AP, MI, and IS suggests that thyroid function assessment could be integral to preventing and diagnosing specific ASCVD types. This underscores the need for individuals with hypothyroidism to be proactive regarding ASCVD risk factors. A balanced Th1/Th2 and Th17/Treg ratio may offer a novel strategy in preventing CAD and enhancing the prognosis for hypothyroid patients.